Oral Health Status and its Determinants among a Group of Iranian Employees - Ghasemi, Hadi; Sohrabi, Noushin; Al-Eshaghi, Nasibeh; Hajabedini, Abbas; Khoshnevisan, Mohammadhossein (Journal of Dental School, 2020)
Objectives This study aimed to assess the oral health status of a group of Telecommunication Company (TCC) employees in Tehran, Iran Methods This cross-sectional study included a convenience sample of 426 employees using the WHO suggested protocol for oral health survey. Data regarding employees' oral health knowledge, behaviors, and status were collected by oral examination and using a self-administered questionnaire. Statistical analysis included the Chi-square test, t-test, and ANOVA. Results The participants’ mean age was 45.89±8.17 years, and 63% were males. The majority of the respondents were aware of the effectiveness of tooth brushing and dental flossing for prevention of oral diseases, and the relationship between oral health and general health. Twice a day tooth-brushing was reported by 28% and daily dental flossing by 48%. Also, 93% of the employees were non-smokers. Their mean DMFT was 12.88±5.56 with the following components: D: 1.40±1.80, M: 2.71±3.57, and F: 8.78±4.77). Filled teeth were more prevalent among women, subjects with higher educational degrees, and the office staff than the technicians. Conclusion The TCC employees seem to enjoy a good level of access and utilization of dental care services considering their high share of filled teeth in their DMFT index. Better maintenance and further improvement of their oral health require comprehensive and continuous oral health promotion programs.